Information as a Source of Empowerment: The Role of Climate Information Services - Kramer, Berber; Trachtman, Carly; Zuze, Linda (2023)
Quantifying the welfare benefits of climate information services (CIS), which provide farmers with weather forecast information and advice can be empirically challenging, given farmers' agricultural investment may increase or decrease depending on the content of the forecast and their levels of risk aversion. In this paper, we quantify the benefits of CIS in terms of the extent that forecast information is able to align a farmer's agricultural investments to those that they would have chosen if they had known the weather realization with full certainty. Specifically, we invite farmers in Zambia to play an app game which asks them to make simulated agricultural investment decisions, with and without CIS information. Additionally, we invite couples to play the game both as individuals and jointly to test whether CIS information can help align individuals' preferred investment choices with jointly made investment decisions.